2021
DOI: 10.1159/000516747
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myeloid Leukemia in a Patient with Hepatitis B Virus Infection: A Case Report

Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative disorder diagnosed by demonstrating the Philadelphia chromosome (Ph) or the BCR-ABL fusion gene. Tyrosine kinase inhibitors (TKIs) are the standard of therapy. There are increasing reports of hepatitis B virus reactivation (HBVr) in patients on this treatment. We report a case of a 46-year-old male patient diagnosed to have CML in the chronic phase and resolved hepatitis B infection. He was treated with imatinib as upfront therapy for CML and with lamivudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The Nested PCR products after amplification using specific primers have been presented to the gel electrophoresis, which showed the bands, as shown in the figures ( 1) and ( 2). The current study demonstrated that each genotype contributes a certain amount to the genotype mixture where the ratio was as follows: genotype D (93%), B (79%), C (64%), A (57%), E (21%), and F (0%), as shown in figure (3). HBV genotyping method developed based on PCR amplification assay utilizing type specific primers capable of recognizing six primary HBV genotypes (A-F) [10].…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The Nested PCR products after amplification using specific primers have been presented to the gel electrophoresis, which showed the bands, as shown in the figures ( 1) and ( 2). The current study demonstrated that each genotype contributes a certain amount to the genotype mixture where the ratio was as follows: genotype D (93%), B (79%), C (64%), A (57%), E (21%), and F (0%), as shown in figure (3). HBV genotyping method developed based on PCR amplification assay utilizing type specific primers capable of recognizing six primary HBV genotypes (A-F) [10].…”
Section: Resultsmentioning
confidence: 72%
“…This could be attributable to viral serum load, the sensitivity and specificity of the ELISA test used, sample size, or geographical location. The results of liver function tests revealed that the levels of ALT, AST, and ALP in patients were high (36.31±12.00, 47.92±21.00, and 100.24±45.92) respectively, than controls as shown in table (3). The sensitivity of ALP(83%) and AST(60%) scored highest than ALT (42%) with significant difference.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation